Pengaruh Audit Tenure, Auditor Switching, Audit Delay Dan Rotasi Audit Terhadap Kualitas Audit Terhadap Kualitas Auditor Dengan Komite Audit Sebagai Variabel Moderasi Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di BEI Periode 2019-2024 - Atika Atika; Mhd Karya Satya Azhar (Journal of Innovative and Creativity, 2025)
This study aims to analyze the effect of audit tenure, auditor switching, audit delay, and audit rotation on audit quality with the audit committee as a moderating variable in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2024. The study applies a quantitative approach using logistic regression and Moderated Regression Analysis (MRA). The sample consists of 20 companies with a total of 120 observations obtained through purposive sampling. The findings reveal that audit tenure has a significant effect on audit quality, while auditor switching shows no effect. Audit delay is proven to influence audit quality both directly and when moderated by the audit committee. Audit rotation has no effect on audit quality, including when moderated by the audit committee. The presence of the audit committee strengthens the effect of audit tenure and audit delay on audit quality but is unable to moderate the influence of auditor switching and audit rotation. These results emphasize that the effectiveness of the audit committee plays a crucial role in maintaining audit quality, particularly in relation to auditor tenure and the timeliness of audit reports. This study provides practical implications for companies, regulators, and auditors in improving audit quality through optimal engagement management, efficient audit processes, and the strengthening of the audit committee’s role.